Basketball Game Shooting Training Model Through Beef Approach - Destriana, Ayu; Hardiyono, Bayu; Sukmawati, Noviria; Fikri, Afrizal; Muslimin, Muslimin (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
This research aims to produce a basketball shooting training model using the BEEF approach and improve the BEEF training model to improve basketball shooting skills. To carry out a shot requires coordination from the body to the fingertips, which is called BEEF. The research method used in this research is a quantitative research method by carrying out pretest and posttest tests to obtain data on students' shooting abilities. The population of this study were students of SMP Negeri 1 Tanjung Raja who took part in basketball extracurriculars with a sample size of 20 people. The results of the data obtained were then carried out with a Normality test, obtained .166 > 0.05 (pre-test) and 0.065> 0.05 (post-test). Hypothesis. Based on the SPSS results that have been carried out, it was found that the hypothesis test was significantly smaller than 0.05 (sig<0.05) stating that there was an influence of providing a training model with the BEEF approach on students' shooting abilities.